STRATEGI PEMBELAJARAN BERBASIS KESADARAN DIRI (SELF-AWARENESS LEARNING) PADA PESERTA DIDIK ERA DIGITAL - Salwa Muin; Bambang Triawan Pamungkas; Fatikhatun Nur; Malikhah Nur Laili; Elok Widiana Sukmawati (LPPM Universitas Nias Raya, 2026)
Digital transformation poses challenges to students’ self-regulation, metacognition, and emotional stability within distraction-rich learning environments. This study aims to formulate an integrative and contextual Self-Awareness Learning strategy for the digital era. A qualitative approach with a systematic literature review (SLR) design was employed, guided by the PRISMA 2020 framework. Data sources included peer-reviewed journal articles, academic books, and educational policy documents addressing self-regulated learning, metacognition, social-emotional learning, and digital learning. Data were analyzed using thematic analysis, and trustworthiness was ensured through credibility, dependability, and confirmability procedures. The synthesis produced a five-component conceptual model: Cognitive Awareness, Metacognitive Regulation, Emotional Awareness, Reflective Integration, and Digital Adaptation Layer. The findings emphasize that effective learning requires the systemic integration of reflective epistemic processes and digital adaptability. The study recommends implementing structured reflective cycles in formal instructional design.